The Influence of Applying Picture Word Inductive Model (PWIM) and Learning Motivation Towards the Students’ Writing Interest on Descriptive Text at SMP Negeri 1 Sembawa - Febriyanti, Marsilia; Syahri, Indawan; Mulyad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study discusses about the influence of applying Picture Word Inductive Model (PWIM) and learning motivation towards the students’ writing interest on descriptive text at SMP Negeri 1 Sembawa. Pictures are just a medium to draw students' interest. Strategy is needed to make the understanding of the material come to students easier. Visual materials have main function to help create a situation become interesting in language lesson. There is comprehension and intuition of students with varying interpretations that can be built. PWIM is a strategy which allows the students to use their imagination to make sentences based on the words/phrases provided in the picture. The pictures used are associated with words describing familiar objects and the student find words out. The words will help the students to have idea in writing sentences while seeing the picture associated with words/phrases. Interest is being one of the important factors in order to increase the students’ comprehension achievement in writing.